Impact Assessment of Emissions Stabilization Scenarios with and without Induced Technological Change - Claudia Kemfert; Truong Phuoc Truong (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The main aim of this paper is to investigate quantitatively the economic impacts of emissions stabilization scenarios with and without the inclusion of induced technological change (ITC). Improved technological innovations are triggered by increased R&D expenditures that advance energy efficiencies. Model results show that induced technological changes due to increased investment in R&D reduce compliance costs. Although R&D expenditures compete with other investment expenditures, we find that increased R&D expenditures improve energy efficiency which substantially lowers abatement costs. Without the inclusion of induced technological change, emissions targets are primarily reached by declines in production, resulting in overall welfare reductions. With the inclusion of induced technological changes, emissions mitigations can result in fewer production and GDP drawbacks.
Keywords: Q4; O3; C6; D5; 330; impact assessment of climate policy; technological change